We need to solve the following system:
![\begin{cases}6x-y=18 \\ 4x+2y=26\end{cases}](https://img.qammunity.org/2023/formulas/mathematics/college/e3verdgxw06svjm9di3865q2ewn7aqiwsc.png)
We need to select the steps that leads us to solving the system.
The first option says that we need to multiply the first equation by 2 then subtract the second equation from the result. Let's see how this goes:
![\begin{gathered} \begin{cases}(6x-y=18)\cdot2 \\ 4x+2y=26\end{cases} \\ \begin{cases}12x-2y=36 \\ 4x+2y=26\end{cases} \\ 12x-4x-2y-2y=36-26 \\ 8x-4y=10 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/y85e1h2oe16y9qf7pbke8ejf5iy8tuk6r5.png)
This does not eliminate one variable, therefore it's incorrect.
The second option tells us to multiply the first equation by 4 and the second by 6, then subtract the resulting equations:
![\begin{gathered} \begin{cases}(6x-y=18)\cdot4 \\ (4x+2y=26)\cdot6\end{cases} \\ \begin{cases}24x-4y=72 \\ 24x+12y=156\end{cases} \\ 24x-24x-4y-12y=72-156 \\ -16y=-84 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ibw9w1r0pte2hyujqrdookk7agapp7wi3t.png)
This eliminates one variable, therefore it is correct.
The third option tells us to multiply the first equation by 2, then add the result to the second equation.
![\begin{gathered} \begin{cases}(6x-y=18)\cdot2 \\ 4x+2y=26\end{cases} \\ \begin{cases}12x-2y=36 \\ 4x+2y=26\end{cases} \\ 12x+4x-2y+2y=36+26 \\ 16x=62 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/c7lpwwuerbof3pxb7nuk0qcs582jf5nwl0.png)
This elimates one variable, therefore it is correct.
The fourth option tells us to divide the second equation by 2, then add the result to the first equation.
![\begin{gathered} \begin{cases}6x-y=18 \\ (4x+2y=26)\colon2\end{cases} \\ \begin{cases}6x-y=18 \\ 2x+y=13\end{cases} \\ 6x+2x-y+y=18+13 \\ 8x=31 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/m706ypj05q8v1en3ijdkfc1lbtjworuoxu.png)
Since this eliminates one variable, it is correct.
The fith option tells us to multiply the second equation by 6, then subtract the result from the frist equation.
![\begin{gathered} \begin{cases}6x-y=18 \\ (4x+2y=26)\cdot6\end{cases} \\ \begin{cases}6x-y=18 \\ 24x+12y=156\end{cases} \\ 6x-24x-y-12y=18-156 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/32lbd9odeijiswjmqwut6r71p80rejrzff.png)
This does not eliminates one variable, it is incorrect.
The correct options are: 2, 3 and 4.